1988
DOI: 10.1159/000138364
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Dietary Treatment with L-Tryptophan on the Development of Renal Hypertension in Rats

Abstract: Chronic dietary administration of L-tryptophan (2.5 and 5.0 g/100 g food) to rats provided significant protection against the development of hypertension induced by bilateral encapsulation of the kidneys with latex envelopes. Lower doses of tryptophan (0.5 and 1.0 g/100 g food) attenuated the rate of elevation of blood pressure, but failed to maintain systolic blood pressures at levels significantly below that of untreated renal hypertensive controls. The body weight of the rats was not affected significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1988
1988
1995
1995

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Earlier studies from this laboratory have demonstrated that chronic dietary adminis tration of L-tryptophan can either attenuate or prevent the development of deoxycorti costerone acetate (DOCA)-induced, renalinduced, and spontaneous (genetic) hyper tensions in rats [11,12,14,16]. Others have shown that similar treatment attenuated the development of hypertension in DS rats [23].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies from this laboratory have demonstrated that chronic dietary adminis tration of L-tryptophan can either attenuate or prevent the development of deoxycorti costerone acetate (DOCA)-induced, renalinduced, and spontaneous (genetic) hyper tensions in rats [11,12,14,16]. Others have shown that similar treatment attenuated the development of hypertension in DS rats [23].…”
Section: Introductionmentioning
confidence: 99%
“…The significant interac tion of these two compounds in attenuating the elevation of blood pressure, mentioned above, suggests that the mechanisms involved are different, such that the combination of the two drugs results in greater responses than would be expected from the summation of the two individual responses. Additional studies from this and other lab oratories have shown that chronic treatment with tryptophan protects against the develop ment of DOCA-induced, Dahl salt-sensitive, spontaneously induced, renal-induced, and cold-induced hypertensions in rats [1][2][3][4][9][10][11][12][13]. In addition, chronic administration of tryptophan to humans with borderline essen tial hypertension has been shown to reduce blood pressure [14,15].…”
Section: Discussionmentioning
confidence: 85%
“…These include DOCA-induced [1,3], renal-induced [2], spontaneous [4] and Dahl salt-induced hy pertensions [5]. In addition, metabolites of L-tryptophan were shown to have antihyper tensive effects, supporting the hypothesis that L-tryptophan may exert its antihyper tensive effects either by conversion to 5-hydroxytryptamine (serotonin) [8] or by con version to other metabolites like nicotinic acid [24] and indole-3-pyruvic acid [25].…”
Section: Discussionmentioning
confidence: 88%
“…Earlier studies from this laboratory showed that chronic dietary administration of the neutral amino acid, L-tryptophan, can either attenuate or prevent the development of deoxycorticosterone acetate (DOCA)-induced, renal-induced, and spontaneous (ge netic) hypertensions in rats [1][2][3][4]. Others showed that similar treatment attenuated the development of hypertension in Dahl salt-sensitive rats [5].…”
Section: Introductionmentioning
confidence: 99%